MACRO COHERENCE LEVEL ON STUDENTS’ SCIENTIFIC PAPER - Leora Grahadila Andovita; Aceng Rahmat; Hanif Pujiati (UNIVERSITAS PAKUAN, 2019)
Purposely contemplating at seventh semester students of English Education Study Progam, it is perceived that students exhibit a lack of skills in use of rhetoric, predominantly making errors in the use of words and phrases, directly translating words from Bahasa Indonesia to English – interlanguage error – and organizing their written text inadequately. Moreover, it is discovered that the viewpoints of the students frequently shift. To address this, this current study aims at investigating students’ macro-level coherence in their academic writing (henceforth; background of the study of a research proposal). A content analysis is applied including documents. Additionally, a descriptive analysis design is used to guide this study. There are six research proposals investigated to gain the data of this study. These proposals are taken purposively sampled from proposals submission from early 2018 intake. There are two main frameworks in this study. Firstly, the academic writing guidance book is used to analyze the rhetoric/organization of the paper. Secondly, the coherence analysis is applied to evaluate students’ coherence level. Analysis of findings shows that students encounter some problems in the coherence of English research proposal writing. Hence, it is argued that close attention should be paid to the refinement and suitable tutoring of coherence in the teaching of academic English writing